Monocyte to High-Density Lipoprotein Cholesterol Ratio at the Nexus of Type 2 Diabetes Mellitus Patients With Metabolic-Associated Fatty Liver Disease - Jia, Jue; Liu, Ruoshuang; Wei, Weiping; Yu, Fan; Yu, Xiawen; Shen, Yirong; Chen, Caiqin; Cai, Zhensheng; Wang, Chenxi; Zhao, Zhicong; Wang, Dong; Yang, Ling; et al. (Frontiers in Physiology, 2021)
Background: Recently, monocyte to high-density lipoprotein cholesterol ratio (MHR) as a novel inflammatory biomarker has drawn lots of attention. This study was conducted in patients with type 2 diabetes mellitus (T2DM) to investigate the correlation between MHR and metabolic-associated fatty liver disease (MAFLD). Methods: Totally, 1,051 patients with T2DM from the Affiliated Hospital of Jiangsu University were enrolled and classified as MAFLD (n = 745) group and non-MAFLD (n = 306) group according to the MAFLD diagnostic criteria. In contrast, patients were also separated into four groups based on MHR quartiles. Anthropometric and biochemical measurements were performed. The visceral fat area (VFA) and subcutaneous fat area (SFA) of participants were measured by dual bioelectrical impedance. Fatty liver was assessed by ultrasonography. Results: The MHR level of subjects in the MAFLD group was statistically greater than that in the non-MAFLD group (P < 0.05). Meanwhile, MHR was higher in the overweight or obese MAFLD group compared with that in the lean MAFLD group (P < 0.05). The area under the ROC Curve (AUC) assessed by MHR was larger than that of other inflammatory markers (P < 0.01). The cutoff value of MHR was 0.388, with a sensitivity of 61.74% and a specificity of 56.54%. For further study, binary logistic regression analyses of MAFLD as a dependent variable, the relationship between MHR and MAFLD was significant (P < 0.01). After adjusting for many factors, the relationship still existed. In the four groups based on MHR quartiles, groups with higher values of MHR had a significantly higher prevalence of MAFLD (P < 0.05). The percentage of patients with obese MAFLD increased as the MHR level increased (P < 0.01). Among different quartiles of MHR, it showed that with the increasing of MHR, the percentage of patients with MAFLD who had more than four metabolic dysfunction indicators increased, which was 46.39, 60.52, 66.79, and 79.91%, respectively, in each quartile. Conclusion: Monocyte to high-density lipoprotein cholesterol ratio is a simple and practicable inflammatory parameter that could be used for assessing MAFLD in T2DM. T2DM patients with higher MHR have more possibility to be diagnosed as MAFLD. Therefore, more attention should be given to the indicator in the examination of T2DM.